Compatibility and Kidney Transplantation: The Way to Go - Doxiadis, Ilias I.N. (Frontiers in Immunology, 2012)
Long lasting debates in the past questioned the relevance of any sort of compatibility in post mortal kidney transplantation. It is for no say that fully compatible transplants have the highest chances for a long patient and graft survival. In the present report the use of HLA-DR as a representative of the Major Histocompatibility Complex class II genes in the allocation of organs is discussed. The major arguments are the easiness to offer to patients a compatible graft in a relatively short waiting time, an increase in graft survival, the less sensitization during the transplantation period, and the lower waiting time for a retransplant. Even if the number of organ donors remains the same a lowering of the mean waiting time is expected because of the longer period of graft survival.